Finding Eden - Sheridan, Mia (Naperville, Illinois : Bloom Books, 2023)
"Calder and Eden are free from the stifling grasp of Acadia, but the new world they've stepped into is just as isolating. Each convinced the other died in the flood that decimated their community, they're forced into modern life, hearts broken, futures unclear. After all they sacrificed to be together, a life without one another, forever haunted by grief and memories, seems impossible to bear. But they do bear it. They survive. And when they meet by chance years later, happiness, for once, finally seems within their grasp. Still, the past is a bright, burning pain between them, and Calder and Eden cannot truly move on until they lay it to rest. With Acadia's story forced into the public eye and dangerous questions mounting, the two must untangle the truths of the life they came from to discover who they are and who they might become together. Only, what they discover might drown them for good"--
Keywords: Romance fiction; Novels